2023
DOI: 10.1002/ccd.30602
|View full text |Cite
|
Sign up to set email alerts
|

Distal versus conventional radial artery access for coronary catheterization: A systematic review and meta‐analysis

Abstract: Background The distal radial artery (DRA) access is an alternative to the conventional radial artery (CRA) access for coronary angiography and interventions and appears to be associated with reduced incidence of certain outcomes. Methods A systematic review was performed to evaluate differences between DRA versus CRA access for coronary angiography and/or interventions. Following preferred reporting items for systematic review and meta‐analysis‐protocols guidelines, two reviewers independently selected studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Conversely, the conventional trans-radial puncture site is usually on a straighter artery segment. In a meta-analysis by Feghaly et al, there was no statistically significant difference between distal radial access and conventional radial access in terms of fluoroscopy time and contrast doses [ 12 ]. Similarly, in our study, no significant differences were observed between the distal radial site and the conventional radial site regarding fluoroscopy time (p=0.183) and contrast volume (p=0.345).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the conventional trans-radial puncture site is usually on a straighter artery segment. In a meta-analysis by Feghaly et al, there was no statistically significant difference between distal radial access and conventional radial access in terms of fluoroscopy time and contrast doses [ 12 ]. Similarly, in our study, no significant differences were observed between the distal radial site and the conventional radial site regarding fluoroscopy time (p=0.183) and contrast volume (p=0.345).…”
Section: Discussionmentioning
confidence: 99%
“…This may be because the distal trans-radial access carries a lower risk of retrograde thrombus formation, given the collateral blood flow from the superficial palmar arch compared to the forearm trans-radial artery. Additionally, branches arising from the radial artery before the anatomic snuffbox form anastomoses with other wrist vessels, ensuring distal blood flow even in the presence of puncture-related ischemic complications [ 12 ]. In this study, a lower incidence of RAO was observed in the distal trans-radial access compared to the conventional trans-radial access (2% vs. 13%; p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The putative mechanism for this hypothesis is the more distal location of the puncture site, which in turn may facilitate greater preservation of flow in the radial artery proximally, due to the rich cascade of adjacent collateral networks from the deep palmar arch. The safety and feasibility of dTRA for coronary angiography and PCI has been demonstrated, with clinical trial data suggesting greater reductions in RAO, as determined by doppler ultrasound, compared to traditional TRA (84,85). Little is known, however, regarding the pathobiology of radial artery injury and remodeling following dTRA.…”
Section: Distal Transradial Accessmentioning
confidence: 99%
“…differences in DRA and conventional radial arterial (CRA) access with respect to procedural and clinical outcomes. 3…”
Section: Key Pointsmentioning
confidence: 99%
“…To this end, several recent randomized control trials, case‐control studies, and observational studies have sought to investigate the real‐world efficacy and complication rate of DRA access, with varying results. In this issue of Catheterization and Cardiovascular Intervention, Feghaly et al provide the largest systematic review to date assessing the differences in DRA and conventional radial arterial (CRA) access with respect to procedural and clinical outcomes 3 . Their systemic review and meta‐analysis included 28 studies with a total of 9151 patients [4474 DRA patients and 4677 CRA patients].…”
mentioning
confidence: 99%